A p-type silicon carbide crystal
Patent Information
- Application Number
- CN202311099315.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-08-29
AI Technical Summary
但上述方法只能在一定程度上减小生长前后期晶体中掺杂剂量差异,在实际的PVT法制备P型碳化硅晶体制备过程中,受固相掺杂剂浓度的降低及晶体生长过程的不可控性,沿晶锭生长方向随着生长的进行而出现掺杂物质浓度逐渐降低的现象不可避免
[0008] (1) The P-type silicon carbide crystal of the present invention has more uniform doping, more uniform resistivity, and higher and more uniform crystal transmittance.
Smart Images

Figure CN117305983B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicon carbide crystal growth technology, and more specifically, to a P-type silicon carbide crystal. Background Technology
[0002] Silicon carbide (Silicon carbide) is a third-generation semiconductor material, a wide-bandgap semiconductor material following the first-generation elemental semiconductors silicon and germanium, and the second-generation compound semiconductors gallium arsenide and indium phosphide. Compared with the previous two generations of semiconductor materials, silicon carbide has better physical and electronic properties and chemical stability. It has high thermal conductivity, a strong breakdown field, and a high saturated electron drift velocity, thus showing broad prospects in the fabrication and application of high-temperature, high-frequency, high-power, and corrosion-resistant radiation-resistant devices, and is widely used in defense, aerospace, communications, and other fields.
[0003] The fabrication of microelectronic devices requires crystals with high p-type or n-type doping concentrations. Doping can be achieved through raw material doping during crystal growth or through methods such as ion implantation. To achieve optimal electronic performance, the doped ions need to be in an activated state; the activation energy of doped ions in different materials is temperature-dependent. Silicon can achieve doped ion activation at room temperature, while silicon carbide has relatively high doped ion activation energies.
[0004] In the current PVT method for preparing p-type silicon carbide crystals, elemental boron / aluminum or its compounds are typically used for doping. Due to the high melting and boiling points of boron / aluminum or its compounds, they exist in solid form at room temperature and pressure, and partially in gaseous form under high pressure at room temperature, but none at room temperature. Therefore, solid-phase doping is currently used in the PVT method for preparing p-type silicon carbide crystals. The main methods involve improving the placement of the dopant source, the container holding the dopant source, and controlling the temperature of the dopant source region individually through thermal field modifications (such as a dual-coil structure) to slow down dopant release in the early stages of growth and increase dopant release in the later stages, aiming to minimize the difference in dopant concentration between the early and late stages of growth. However, these methods can only reduce the difference in dopant concentration to a certain extent. In the actual PVT process for preparing p-type silicon carbide crystals, the decreasing concentration of the solid-phase dopant and the uncontrollable nature of the crystal growth process inevitably lead to a gradual decrease in dopant concentration along the ingot growth direction as growth progresses. Summary of the Invention
[0005] The inventors discovered that during the PVT process for preparing p-type silicon carbide crystals, the decreasing concentration of the solid-phase dopant and the uncontrollable nature of the crystal growth process inevitably lead to a gradual decrease in dopant concentration along the ingot growth direction as growth progresses. Furthermore, the presence of unintentionally added nitrogen can occur due to environmental factors. These two factors result in low substrate resistivity in the early stages of crystal formation, followed by a gradual increase in resistivity in the later stages, and even a change in conductivity type, affecting the resistivity uniformity and electrical properties of the p-type substrate. Therefore, from a practical application perspective, it is necessary to improve the uniformity of doping concentration in the p-type substrate, especially the axial uniformity of doping concentration between the early and later stages of crystal formation, thereby improving the uniformity of substrate resistivity.
[0006] This invention provides a p-type silicon carbide crystal, wherein the maximum resistivity of the p-type silicon carbide crystal is ≤3Ω*cm, the axial resistivity change rate at the same radial position is ≤25%, and the p-type element impurity content is ≥1E. 17 atoms / cm 3 The change rate of P-type elemental impurities is ≤15%.
[0007] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:
[0008] (1) The P-type silicon carbide crystal of the present invention has more uniform doping, more uniform resistivity, and higher and more uniform crystal transmittance.
[0009] (2) This invention establishes the correlation between the amount of doping in a crystal and the color of the crystal.
[0010] (3) The axial resistivity change rate at the same radial position of the P-type silicon carbide crystal of the present invention is ≤25%, and the content of P-type elemental impurities is ≥1E. 17 atoms / cm 3 The variation rate of P-type elemental impurities is ≤15%. Preferably, the variation rate of axial resistivity at the same radial position in the P-type silicon carbide crystal of the present invention is ≤10%, and the variation rate of P-type elemental impurities is ≤10%. Attached Figure Description
[0011] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings:
[0012] Figure 1 An exemplary embodiment of the P-type silicon carbide crystal growth device of the present invention is shown in the schematic diagram.
[0013] Figure 2 This indicates that the Al doping concentration in the crystal is greater than 1E. 15 And less than or equal to 1E 16atoms / cm 3 An exemplary embodiment of the axial distribution curve of Al content at time;
[0014] Figure 3 This indicates that the Al doping concentration in the crystal is greater than 1E. 15 And less than or equal to 1E 16 atoms / cm 3 An exemplary embodiment of the axial resistivity variation curve of a crystal.
[0015] Figure 4 This indicates that the Al doping concentration in the crystal is greater than 1E. 18 And less than or equal to 1E 19 atoms / cm 3 An exemplary embodiment of the axial distribution curve of Al content at time;
[0016] Figure 5-1 This indicates that the Al doping concentration in the crystal is greater than 1E. 18 And less than or equal to 1E 19 atoms / cm 3 An exemplary embodiment of the axial resistivity variation curve of a crystal over time;
[0017] Figure 5-2 for Figure 5-1 Magnified view of gas-phase doping;
[0018] Figure 6 This indicates that the Al doping concentration in the crystal is greater than 1E. 20 And less than or equal to 1E 21 atoms / cm 3 An exemplary embodiment of the axial distribution curve of Al content at time;
[0019] Figure 7 This indicates that the Al doping concentration in the crystal is greater than 1E. 20 And less than or equal to 1E 21 atoms / cm 3 An exemplary embodiment of the axial resistivity variation curve of a crystal over time;
[0020] Figure 8 This indicates that the boron doping level in the crystal is greater than 1E. 18 And less than or equal to 1E 19 atoms / cm 3 An exemplary embodiment of the axial distribution curve of B content in a crystal;
[0021] Figure 9 This indicates that the boron doping level in the crystal is greater than 1E. 18 And less than or equal to 1E 19 atoms / cm3 An exemplary embodiment of the axial resistivity variation curve of a crystal.
[0022] Explanation of reference numerals in the attached figures:
[0023] 1-Outer shell; 2-Induction coil; 3-Quartz tube; 4-Insulation cylinder; 5-Crystal growth chamber; 6-Seed crystal; 7-Crucible; 8-Evaporator; 9-Doping source; 10-Carrier gas source; 11-Doping source switch 2#; 12-Doping source switch 1#; 13-Carrier gas switch 1#; 14-Carrier gas switch 2#. Detailed Implementation
[0024] To more clearly illustrate the overall concept of the present invention, a detailed description will be provided below with reference to the accompanying drawings and examples.
[0025] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0026] Furthermore, in the description of this invention, it should be understood that the terms "top," "bottom," "inner," "outer," "axial," "radial," "circumferential," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0027] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection, an electrical connection, or a communication connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0028] In this invention, unless otherwise expressly specified and limited, the first feature "on" or "below" the second feature may be in direct contact with the first and second features, or indirect contact through an intermediate medium. In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0029] In a first exemplary embodiment of the present invention, the maximum resistivity of the P-type silicon carbide crystal is ≤3Ω*cm, and the rate of change of axial resistivity at the same radial position is ≤25%; the content of P-type elemental impurities is ≥1E. 17 atoms / cm3, P-type element impurity variation rate ≤15%. Preferably, axial resistivity variation rate at the same radial position ≤10%, P-type element impurity variation rate ≤10%. More preferably, axial resistivity variation rate at the same radial position ≤8%, P-type element impurity variation rate ≤8%.
[0030] The substrate obtained from the p-type silicon carbide crystal was tested using high-resolution XRD rocking curves. The full width at half maximum (FWHM) was ≤30 arcsec, the intra-wafer FWHM variation rate was ≤30%, and the axial FWHM variation rate at the same radial position was ≤20%. Preferably, the intra-wafer FWHM variation rate was ≤20%, and the axial FWHM variation rate at the same radial position was ≤15%. More preferably, the intra-wafer FWHM variation rate was ≤15%, and the axial FWHM variation rate at the same radial position was ≤10%.
[0031] Specifically, the substrate obtained from P-type silicon carbide crystal was characterized by KOH etching, and the total dislocation density was ≤3000 / cm². 2 Through-type dislocation density ≤2500 / cm 2 Preferably, the total dislocation density is ≤2000 / cm². 2 Through-type dislocation density ≤1000 / cm 2 .
[0032] Specifically, the hardness of the P-type silicon carbide crystal is not less than 9.5 Mohs hardness.
[0033] Specifically, the P-type silicon carbide crystal has a visible light transmittance ≥ 0.6 and a refractive index of 2.6–2.8. Preferably, the P-type silicon carbide crystal has a visible light transmittance ≥ 0.8.
[0034] Specifically, the p-type silicon carbide crystal absorbs orange light in the wavelength range of 455–490 nm, and the crystal color is blue. Further, 1E 16 atoms / cm 3 <P-type element impurity content ≤5E 16 atoms / cm 3 The crystals are light blue in color; 5E 16 atoms / cm 3 <P-type element impurity content ≤1E 19 atoms / cm 3 The crystals are sapphire blue or medium blue in color; the content of p-type element impurities in the substrate is >1E. 19 atoms / cm 3 The crystals are dark blue in color.
[0035] Specifically, the preparation method of the above-mentioned P-type silicon carbide crystal includes the following steps:
[0036] (1) Vacuum stage: The crystal growth furnace is evacuated to remove impurity gases from the growth chamber, with a vacuum degree ≤1E. -2 pa;
[0037] (2) Heating and pressurizing stage: After the vacuum stage is completed, carrier gas is introduced into the crystal growth furnace to raise the temperature to above 2000℃ and the pressure to above 10mbar.
[0038] (3) Introducing dopant source: Introducing vaporized dopant source and carrier gas into the crystal growth furnace to perform gas phase doping; furthermore, the concentration of dopant source in the crystal can be controlled by controlling the carrier gas flow rate and the amount of dopant source introduced.
[0039] (4) Nucleation stage: Controlling the temperature near the seed crystal surface to ≥2000℃ and the pressure to ≥10mbar is beneficial to suppressing two-dimensional nucleation and improving the crystal crystal quality;
[0040] (5) Pressure reduction growth stage: control the pressure to be reduced to ≤10mbar and the temperature to ≥2100℃ to obtain P-type silicon carbide crystals.
[0041] The above preparation method is applicable to silicon carbide crystal forms such as 4H, 6H, 15R, and 3C. The dopant source can be a compound containing Al or B. For example, the dopant source can be one of trimethylaluminum, trimethylboron, aluminum chloride, or boron chloride.
[0042] Furthermore, the P-type silicon carbide crystal growth apparatus includes a gas supply unit that provides a doping source to the crystal growth chamber of the crystal growth furnace. The gas supply unit includes at least one carrier gas channel and at least one doping source gas channel. The carrier gas channel is equipped with a carrier gas source, a carrier gas flow monitoring unit, and a carrier gas switch for controlling the opening and closing of the carrier gas channel. The doping source gas channel is equipped with a doping source, a doping source flow monitoring unit, a doping source switch for controlling the opening and closing of the doping source gas channel, and a doping source vaporization unit.
[0043] The carrier gas source is connected to the crystal growth cavity through the carrier gas channel, and the dopant source is connected to the crystal growth cavity through the dopant source gas channel. The dopant source vaporization device enables the dopant source to be vaporized.
[0044] The crystal growth furnace unit includes a crucible, a heat-insulating cylinder, a furnace body, and a crystal growth chamber; wherein, the crucible is placed inside the heat-insulating cylinder, the bottom of the crucible is used to place silicon carbide raw material, and the top of the crucible is used to set seed crystal; the furnace body is used to place the crucible and the heat-insulating cylinder.
[0045] During operation, the carrier gas flow rate and the amount of dopant source can be controlled by the carrier gas flow rate monitoring unit and the dopant source flow rate monitoring unit, thereby controlling the number of dopant sources that finally enter the crystal growth chamber and thus controlling the concentration of dopant sources in the crystal.
[0046] Specifically, the gasification device is an evaporator or a bubbling gas generator. The furnace body includes an inner cavity and an outer shell. A quartz tube is installed on the inner cavity, and an induction coil is installed on the outer shell. This device enables a continuous influx of dopant into the crystal growth chamber, ensuring a stable dopant concentration within the chamber during crystal growth and significantly improving the uniformity of axial dopant concentration in the crystal.
[0047] Examples 2-4
[0048] Based on the first exemplary embodiment, refer to Figure 1 As shown, Figure 1 A schematic diagram of a P-type silicon carbide crystal growth device is shown. The P-type silicon carbide crystal growth device includes:
[0049] The crystal growth furnace unit includes a crucible 7, a heat-insulating cylinder 4, a furnace body, and a crystal growth chamber 5. The crucible 7 is placed inside the heat-insulating cylinder 4, with silicon carbide powder placed at the bottom and a seed crystal 6 placed at the top. The furnace body houses the crucible 7 and the heat-insulating cylinder 4. The furnace body includes an inner cavity and an outer shell 1. A quartz tube 3 is installed on the inner cavity, and an induction coil 2 is installed on the outer shell.
[0050] A gas supply unit for providing doping sources to the crystal growth chamber of the crystal growth furnace includes a carrier gas channel and a doping source gas channel, which merge into a single gas channel near the crystal growth chamber. The carrier gas channel is equipped with a carrier gas source 10, a carrier gas flow monitoring unit, and a carrier gas switch for controlling the on / off state of the channel. The carrier gas switch includes carrier gas switch 1#13 and carrier gas switch 2#14. The doping source gas channel is equipped with a doping source 9, a doping source flow monitoring unit, a doping source switch for controlling the on / off state of the doping source channel, and an evaporator 8. Specifically, the doping source switch includes doping source switch 1#12 and doping source switch 2#11.
[0051] Specifically, the preparation method of the above-mentioned P-type silicon carbide crystal includes the following steps:
[0052] (1) Vacuum stage: The crystal growth furnace is evacuated to a vacuum level ≤1E. -2 Pa, retention time ≥1 hour;
[0053] (2) Heating and pressurizing stage: After the vacuum stage is completed, open the carrier gas switch 1#13 to introduce carrier gas into the crystal growth furnace, heat up to above 2000℃ and pressurize to above 10mbar, and pressurize for ≥2h.
[0054] (3) Introduce the dopant source: Open the carrier gas switch 2#14 and the dopant source switch 1#12 to allow the dopant source and carrier gas to enter the evaporator 8. The dopant source is vaporized. Then open the dopant source switch 2#11 to allow the vaporized dopant source gas and carrier gas to enter the crystal growth furnace cavity 5. Observe the dopant source flow monitoring unit and the carrier gas flow monitoring unit. By adjusting the size of the dopant source switch 2#11, the dopant source switch 1#12 and the carrier gas switch 2#14, the amount of dopant source entering the crystal growth furnace cavity can be controlled, thereby controlling the amount of dopant source in the crystal.
[0055] (4) Nucleation stage: Control the temperature near the seed crystal surface to be ≥2000℃ and the pressure to be ≥10mbar;
[0056] (5) Pressure reduction growth stage: control the pressure to be reduced to ≤10mbar and the temperature to ≥2100℃ to obtain P-type silicon carbide crystals.
[0057] Examples 2-4 show that trimethylaluminum was used as the dopant source for vapor-phase doping, and crystals with different doping amounts were prepared with a thickness of 20 mm. SIMS was used to measure the axial distribution of Al content in the prepared crystals, referring to... Figure 2 , Figure 4 and Figure 6 As shown. Figure 2 , Figure 4 and Figure 6The yellow curve represents the axial distribution curve of Al content in the crystal prepared according to this exemplary embodiment, and the blue curve represents the axial distribution curve of Al content in the crystal prepared by solid-phase doping.
[0058] The axial resistivity at the same radial position in the prepared crystal was measured, with reference to... Figure 3 , Figure 5-1 , Figure 5-2 and Figure 7 As shown. Figure 3 , Figure 5-1 , Figure 5-2 and Figure 7 The yellow curve represents the axial resistivity variation curve of the crystal prepared in this exemplary embodiment, and the blue curve represents the axial resistivity variation curve of the crystal prepared by solid-phase doping.
[0059] The P-type silicon carbide crystal substrates prepared in Examples 2-4 were etched with KOH, resulting in a total dislocation density ≤1000 / cm². 2 Through-type dislocation density ≤900 / cm 2 High-resolution XRD rocking curves were used to test the substrate's full width at half maximum (FWHM) to be ≤15 arcsec, the in-wafer FWHM variation rate to be ≤10%, and the axial FWHM variation rate to be ≤5% at the same radial position.
[0060] P-type silicon carbide crystals have a Mohs hardness of 9.5.
[0061] The crystal has a transmittance of ≥0.6 under visible light and a refractive index of 2.64 to 2.70.
[0062] Example 5
[0063] Based on Examples 2-4, this exemplary embodiment uses trimethylboron as the dopant source for both gas-phase doping and solid-phase doping. SIMS is used to measure the axial distribution of the boron content in the prepared crystal. Figure 8 As shown; the axial resistivity of the prepared crystal was tested, referencing... Figure 9 As shown in the image.
[0064] Figure 8 In the diagram, the yellow curve represents the axial distribution curve of B content in the crystal prepared according to this exemplary embodiment, and the blue curve represents the axial distribution curve of B content in the crystal prepared by solid-phase doping.
[0065] Figure 9 In the diagram, the yellow curve represents the axial resistivity variation curve of the crystal prepared in this exemplary embodiment, and the blue curve represents the axial resistivity variation curve of the crystal prepared by solid-phase doping.
[0066] Experimental Example
[0067] Based on Example 2, the transmittance of the prepared crystal under visible light was tested, as shown in Table 1.
[0068] Table 1 Transmittance Test Table
[0069]
[0070] Referring to Table 1, the transmittance of the P-type silicon carbide crystal prepared in this embodiment is 0.63-0.65. When solid-phase doping is used, the transmittance of the P-type silicon carbide crystal prepared is 0.57-0.61. It can be seen that gas-phase doping can improve the transmittance and uniformity of the crystal.
[0071] The crystals prepared in Examples 2-5 were subjected to calculations of the axial resistivity change rate and the p-type element impurity change rate at the same radial position. The calculation results are shown in Table 2. The crystals prepared in this application were subjected to crystal color testing at wavelengths of 455–490 nm. The crystal color test results are shown in Table 2.
[0072] The formula for calculating the rate of change in this application is: Rate of change = (maximum value - minimum value) / maximum value, where "rate of change of p-type element impurities" = [lg(maximum value) - lg(minimum value)] / lg(maximum value)
[0073] Table 2. Calculation of Axial Resistivity Change Rate and P-type Element Impurity Change Rate
[0074]
[0075] Referring to Examples 2-5, in the crystals prepared by vapor-phase doping in this application, the maximum resistivity is ≤3Ω*cm, the axial resistivity change rate at the same radial position is ≤25%, and the P-type element impurity change rate is ≤10%. In the crystals prepared by solid-phase doping, the maximum resistivity is >6Ω*cm, the axial resistivity change rate at the same radial position is >50%, and the P-type element impurity change rate is >10%. It can be seen that the crystals prepared by vapor-phase doping in this application have more uniform doping and more uniform axial resistivity.
[0076] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A p-type silicon carbide crystal, characterized in that, The maximum resistivity of the P-type silicon carbide crystal is ≤3Ω. cm, axial resistivity change rate at the same radial position ≤25%; P-type element impurity content ≥1E 17 atoms / cm 3 The change rate of P-type elemental impurities is ≤15%; The P-type element impurities in the P-type silicon carbide crystal are introduced through vapor phase doping.
2. The P-type silicon carbide crystal according to claim 1, characterized in that, The rate of change of axial resistivity at the same radial position is ≤10%, and the rate of change of P-type element impurities is ≤10%.
3. The P-type silicon carbide crystal according to claim 1, characterized in that, The P-type silicon carbide crystal has a full width at half maximum (FWHM) of ≤30 arcsec, an intra-wafer FWHM variation rate of ≤30%, and an axial FWHM variation rate of ≤20% at the same radial position.
4. The P-type silicon carbide crystal according to claim 3, characterized in that, The half-width at half-maximum (WHM) variation rate of the P-type silicon carbide crystal within the wafer is ≤15%, and the axial WHM variation rate at the same radial position is ≤10%.
5. The P-type silicon carbide crystal according to claim 1, characterized in that, The P-type silicon carbide crystal has a thickness ≤30mm, a visible light transmittance ≥0.6, and a refractive index of 2.6~2.
8.
6. The P-type silicon carbide crystal according to claim 5, characterized in that, The P-type silicon carbide crystal has a visible light transmittance of ≥0.
8.
7. The P-type silicon carbide crystal according to claim 1, characterized in that, The total dislocation density of the P-type silicon carbide crystal is ≤3000 / cm². 2 Through-type dislocation density ≤2500 / cm 2 .
8. The P-type silicon carbide crystal according to claim 1, characterized in that, The hardness of the P-type silicon carbide crystal is not less than 9.5 Mohs hardness.
9. The p-type silicon carbide crystal according to claim 1, characterized in that, The P-type silicon carbide crystal absorbs orange light in the wavelength range of 455~490nm, and the crystal color is blue.
10. The p-type silicon carbide crystal according to claim 9, characterized in that, 1E 16 atoms / cm 3 <P-type element impurity content ≤5E 16 atoms / cm 3 The crystals are light blue in color; 5E 16 atoms / cm 3 <P-type element impurity content ≤1E 18 atoms / cm 3 The crystals are medium blue or royal blue in color; the content of p-type element impurities is >1E. 19 The crystals have an atomic density of 10 atoms / cm3 and are deep blue in color.
Citation Information
Patent Citations
Low-resistivity P-type 4H-SiC single crystal and preparation method thereof
CN112725894A